(untitled) (Atlas Journal of Biology, 2019)
Various environmental factors have been proposed, such as soil moisture levels, carbon, and nitrate sources to affect the abundance of nitrate reducing (NR) and denitrifying (DN) bacteria. In this study, the strength of the association of the abundance of NR and DN bacteria with various environmental factors is estimated using multivariate statistics. Soil samples were collected from tallgrass prairie soils that had been contaminated with crude oil or brine (e.g. salt water) up to 10 years previously and from parallel uncontaminated sites. The abundance of culturable NR and DN bacteria in the soil samples was estimated by 5-tube MPN method using nitrate broth, while total petroleum hydrocarbons (TPH), sodium chloride, nitrate, and moisture were measured in the contaminated and the parallel uncontaminated sites. Viable heterotrophic bacteria and NR and DN bacteria from all sites were obtained from samples with a broad range of soil moisture (around 10-30% water/g soil) regardless of the source (e.g. site) of the isolates. Our results showed that the abundance of NR and DN bacteria from the contaminated sites was not less than that from the uncontaminated sites and reflected soil moisture, with greater bacterial numbers from wetter soils. Also, current remediation treatments (e.g. nitrate, hay, watering) of contaminated sites sometimes, but not consistently, were associated with greater abundance of NR and DN bacteria. Therefore, no long-term effect of contamination on the abundance of NR and DN bacteria was shown.